THE ANALYSIS OF GOOGLE TRANSLATE ACCURACY IN TRANSLATING PROCEDURAL AND NARRATIVE TEXT - Sumiati; Baharuddin; Agus Saputra (Journal of English Education Forum (JEEF), 2022)
Translation is an activity to interpret a text from one language to another language without changing the content of the translated text. The objectives this research is: (1) to find out the accuracy of Google Translate in translating Procedural Text and Narrative Text and (2) to investigate which of the two text is translated more accurately comparing to the other text. This research uses descriptive qualitative method. There was one text for each text type, that is procedure text entitled “How to Make Special Fried Sandwich” wad divided into 31 sentences, and narrative text entitled “Surabaya” was divided into 20 sentences. The data using the accuracy rating assessment which consist of three categories that is accurate, less accurate, and not accurate. The researcher took three raters in evaluating the output of Google Translate. The result shows that the accuracy of Google translate in translating procedure text is accurate with average value of 79.57%, less accurate is 24.19%, and not accurate is 12.9%. And narrative text is accurate with average value of 86%, less accurate is 12.5%, and not accurate is 1.5%. It can be concluded that Google translate is more accurate in translating narrative text with 86%, whereas the procedure text is 79.57%.